2018
DOI: 10.3390/ijms19041249
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and the Function of Argonaute3 in RNAi Pathway of Plutella xylostella

Abstract: Argonaute (Ago) protein family plays a key role in the RNA interference (RNAi) process in different insects including Lepidopteran. However, the role of Ago proteins in the RNAi pathway of Plutella xylostella is still unknown. We cloned an Argonaute3 gene in P. xylostella (PxAgo3) with the complete coding sequence of 2832 bp. The encoded protein had 935 amino acids with an expected molecular weight of 108.9 kDa and an isoelectric point of 9.29. It contained a PAZ (PIWI/Argonaute/Zwile) domain and PIWI (P-eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The diamondback moth, Plutella xylostella , is a highly destructive pest of cruciferous plants worldwide. Nowadays, P. xylostella has become a model species in lepidopteran insects owing to its high fecundity rate and fast dispersal (Hameed et al ., ; Huang et al ., ; Wang et al ., ). The identification of sex‐, stage‐, tissue‐ and germline‐specific cis ‐regulatory elements provides a way for precise gene manipulation in lepidopteran insects.…”
Section: Introductionmentioning
confidence: 99%
“…The diamondback moth, Plutella xylostella , is a highly destructive pest of cruciferous plants worldwide. Nowadays, P. xylostella has become a model species in lepidopteran insects owing to its high fecundity rate and fast dispersal (Hameed et al ., ; Huang et al ., ; Wang et al ., ). The identification of sex‐, stage‐, tissue‐ and germline‐specific cis ‐regulatory elements provides a way for precise gene manipulation in lepidopteran insects.…”
Section: Introductionmentioning
confidence: 99%
“…Although RNAi was used for functional genetic research in insects of many orders, RNAi efficiency was reported to vary among species (Terenius et al ., 2011; Zhang et al ., 2017). Although successful RNAi effects have been reported in insects of many families of Lepidoptera such as Sphingidae, Noctuidae, Plutellidae, Tortricidae and Papilionidae (Choi and Vander, 2019; Christiaens et al ., 2018; Hameed et al ., 2018; Poreddy et al ., 2017; Wang et al ., 2012; Wang et al ., 2015), RNAi efficiency was reported to be relatively low in Lepidoptera, especially compared with the high RNAi sensitivity of Coleoptera and Diptera (Zhang et al ., 2017). Here we showed the effectiveness of transgene triggered RNAi effects on the Noctuidae insect M. separata , with HIGS effects comparable to those for other lepidopteran insects such as Manduca sexta and Helicoverpa armigera (Mao et al ., 2007; Poreddy et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic Tree and Sequence Analysis Ago protein sequences were downloaded from the GenBank database of NONCODE () and NCBI () (43). A multiple-sequence alignment was performed based on the PIWI domain using ClustalW software (version 2.1) (44).…”
Section: Methodsmentioning
confidence: 99%